Comparison of visual outcomes, spectacles dependence and patient satisfaction of multifocal and accommodative intraocular lenses: innovative perspectives for maximal refractive-oriented cataract surgery. Issue 1 (December 2017) - Nuzzi, Raffaele; Tridico, Federico
Abstract Background The aim of this study was to evaluate visual outcomes for different working distances (far, 60 cm and 33 cm) and impact on vision quality of multifocal IOLs AcrySof ResTOR SN6AD1 and SN6AD3 (Alcon, Inc., Fort Worth, Texas, USA) as well as REVIEW FIL611PV multifocal and OPTOFLEX FIL618 accommodative IOLs (Soleko, Ltd., Rome, Italy) in patients undergoing bilateral phacoemulsification. Methods In this observational prospective study 63 patients undergoing binocular cataract surgery were divided into four groups for implantation of one of the IOLs under evaluation. Visual outcomes were evaluated at 1 day, 7 days, 1 month, 3 months and 6 months after surgery. Patients' satisfaction and spectacle independence were evaluated with questionnaires administered at the 6-months follow-up. Results Improvements in visual acuity for the three working distances were statistically significant in all cases compared to the preoperative status, especially after binocular implantation. The AcrySof ReSTOR SN6AD1 multifocal IOL provided the best visual acuity results and tolerability for all working distances. While performing worse than SN6AD1, FIL611PV and FIL618 provided better uncorrected visual acuity and spectacles independence for intermediate/close-up and far distances respectively, in comparison with the SN6AD3 group. Conclusions SN6AD1 was confirmed the best choice for all working distances. However, FIL611PV IOL may represent a valid and more cost-effective alternative, especially if surgeons intend to prioritize spectacle independence and patient autonomy at intermediate and close-up distances, in accordance to specific needs and requests. Trial registration Trial retrospectively registered in ISRCTN Registry on 02/02/2017. TRN:ISRCTN14145737 .